1998
DOI: 10.1002/(sici)1521-4141(199801)28:01<30::aid-immu30>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Primary B cells essentially lack constitutive NF-κB activity

Abstract: Based primarily on the analysis of B cell lines, mature B cells are considered distinct from non-B cells and immature B cells by having constitutive nuclear NF-kappaB activity. By their comparison to splenic non-B cells or activated B cells we show here that primary resting B cells lack cell-autonomous NF-kappaB activity. This finding indicates that the role of the transcription factor in B cells is similar to that in other cells, namely a common mediator of activation and stress signals. Whereas the absence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…This would be in agreement with previous studies with 70Z/ 3 cells, where TGF-L treatment of LPS-stimulated cells blocked both U gene and Oct-2 expression but not NF-UB activation, demonstrating that NF-UB by itself is necessary but not su¤cient to induce U gene expression [24]. Our failure to detect NF-UB in mature 70Z/3 cells is consistent with the ¢nding that primary splenic mouse B cells lack constitutive NF-UB binding activity [25], suggesting that the role of NF-UB in B cells could be important for developmental cellular processes but not for the maintenance of the di¡erentiated phenotype.…”
Section: Discussionsupporting
confidence: 93%
“…This would be in agreement with previous studies with 70Z/ 3 cells, where TGF-L treatment of LPS-stimulated cells blocked both U gene and Oct-2 expression but not NF-UB activation, demonstrating that NF-UB by itself is necessary but not su¤cient to induce U gene expression [24]. Our failure to detect NF-UB in mature 70Z/3 cells is consistent with the ¢nding that primary splenic mouse B cells lack constitutive NF-UB binding activity [25], suggesting that the role of NF-UB in B cells could be important for developmental cellular processes but not for the maintenance of the di¡erentiated phenotype.…”
Section: Discussionsupporting
confidence: 93%
“…Nuclear extraction was conducted as previously described. 29 Briefly, LPS-stimulated B cells, irradiated or nonirradiated, were washed and resuspended in 200-400 ll hypotonic buffer containing 10 mm Hepes (pH 7AE9), 0AE1 mm ethylenediaminetetraacetic acid (EDTA), 0AE1 mm egtazic acid (EGTA), 10 mm KCl, 1 mm dithiothreitol (DTT), 0AE75 mm spermidine, 0AE15 mm spermine, 20 mm p-nitrophenyl phosphate, 20 mm b-glycerophosphate, 1 mm Na 3 VO 4 , and protease inhibitors (1 mm phenylmethylsulphonyl fluoride, 5 lg ⁄ml leupeptin, and 5 lg ⁄ml peptstatin). After 15 min on ice, 0AE6% NP40 was added and the lysates were further incubated for an additional 5 min and were centrifuged at 13 000 g in a microcentrifuge at 4°.…”
Section: Electrophoretic Mobility Shift Assay (Emsa)mentioning
confidence: 99%
“…For determination of NF-jB activity in nuclear extract, an EMSA was performed as previously described. 29 A synthetic oligonucleotide probe containing nucleotides 2969-2945 of the human CD80 enhancer (5¢-GGGAAAGGGGTTTTCCCAGCAGTCA-3¢), which includes the NF-jB binding site. 28 The probe was annealed with a synthetic nucleotide 5¢-TGACTGCTGGGAAAA CCCCTTT-3¢ to form double-stranded DNA.…”
Section: Electrophoretic Mobility Shift Assay (Emsa)mentioning
confidence: 99%
“…To minimize potential in vitro activation of NF-B during cell preparation (17), all isolation procedures were performed at 4°C or on ice. Spleens isolated from 1-to 2-mo-old female C57BL/6 mice housed at the pathogenfree University of Wisconsin Comprehensive Cancer Center Animal Facility were kept on ice, single cells were manually released, and RBCs were hypotonically lysed with ice-cold water followed by immediate isotonic adjustment with ice-cold 10ϫ PBS.…”
Section: Preparation and Fluorescent Activated Cell Sorting Of Primarmentioning
confidence: 99%
“…To determine whether a novel proteasome-independent pathway mediates NF-B activity in vivo, we isolated primary B lymphocytes from murine spleen while minimizing the potential in vitro activation (17) by maintaining the isolation procedures at 4°C. In agreement with prior reports (5, 6), we found that the majority of constitutive NF-B DNA-binding activity observed in primary splenocytes is derived from the B cell compartment (data not shown).…”
Section: Maintenance Of Constitutive Nf-b Activity In Primary Splenocmentioning
confidence: 99%